Community-based wound management in a rural setting of Côte d’Ivoire - Toppino, Simone; Koffi, Didier Yao; Kone, Bognan Valentin; N’Krumah, Raymond T. A. S.; Coulibaly, Ismaël Dognimin; Tobian, Frank; Pluschke, Gerd; Stojković, Marija; Bonfoh, Bassirou; Junghanss, Thomas (PLoS neglected tropical diseases, 2022)
Background Wounds are a neglected health problem in rural communities of low-income countries, mostly caused by trauma and ulcerative skin diseases including Neglected Tropical Diseases (NTDs) and associated with systemic complications and disability. Rural communities have limited access to high quality health services-based wound care. Methods We conducted a prospective observational study on wound management at three levels-community (C), health centre (HC), district hospital (DH)—in a rural community of Côte d’Ivoire. Patients with skin wounds actively identified in a house-to-house survey and passively in the health services in a defined area of the Taabo Health and Demographic Surveillance System were asked to participate and followed-up longitudinally. Endpoints were proportion of wounds closed, time to wound closure, wound size over time, frequency of secondary bacterial infection, need for recapturing after follow-up interruption, and duration of treatment stratified by health service level and wound aetiology. Results We enrolled 561 patients with 923 wounds between May 2019 and March 2020. The observation period ended in March 2021. Median age was 10 years (IQR 7-15), 63.0% of patients were male. Almost all (99.5%, 870/874) wounds closed within the observation period, 5.3% (49/923) were lost to follow-up. Wounds primarily treated in C, HC and DH closed within a median time of 10, 16 and 170 days, respectively. Median time to acute wound and chronic wound closure was 13 and 72 days, respectively. Wounds treated in C, HC and DH presented with secondary bacterial infections in 10.3% (36/350), 31.0% (133/429) and 100% (5/5) of cases, respectively. Recapturing was required in 68.3% (630/923) of wounds with participants reporting wound closure as the main reason for not attending follow-up. Conclusions We describe a wound management model based on national and WHO recommendations focusing on early identification and treatment in the community with potential for broad implementation in low-income countries. Trial registration Registration at ClinicalTrials.gov (NCT03957447).